2020
DOI: 10.1007/s00415-020-09893-2
|View full text |Cite
|
Sign up to set email alerts
|

Independent domains of daily mobility in patients with neurological gait disorders

Abstract: The aim of this study was to establish a comprehensive and yet parsimonious model of daily mobility activity in patients with neurological gait disorders. Patients (N = 240) with early-stage neurological (peripheral vestibular, cerebellar, hypokinetic, vascular or functional) gait disorders and healthy controls (N = 35) were clinically assessed with standardized scores related to functional mobility, balance confidence, quality of life, cognitive function, and fall history. Subsequently, daily mobility was rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 46 publications
0
11
0
1
Order By: Relevance
“…Moreover, the context of the environment is different at home or outdoor where there are multiple obstacles and more complexity compared to the clinical setting 27,28 . Therefore, unsupervised assessments at home can provide additional information through long-term monitoring 29 . Furthermore, it would also be possible to capture rare incidents such as falls or stage before an injury which may not be measurable during a clinical visit.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the context of the environment is different at home or outdoor where there are multiple obstacles and more complexity compared to the clinical setting 27,28 . Therefore, unsupervised assessments at home can provide additional information through long-term monitoring 29 . Furthermore, it would also be possible to capture rare incidents such as falls or stage before an injury which may not be measurable during a clinical visit.…”
Section: Introductionmentioning
confidence: 99%
“…The need to reduce the number of gait metrics to a more manageable size, while retaining as much of the original information as possible has previously led to the development of several conceptual gait models. In particular, these models have been proposed for community-dwelling older adults [28]- [30], older adults with mild cognitive impairment syndromes [31], people with dementia [32], people with Parkinson's disease (PD) [33]- [36], people with early-stage neurological (peripheral vestibular, cerebellar, hypokinetic, vascular or functional) gait disorders [37], and people with hip fracture [38]. Overall, these studies showed that gait characteristics of different cohorts do not consistently load onto identical domains.…”
Section: Introduction Ultiple Sclerosis (Ms) Is An Inflammatorymentioning
confidence: 99%
“…As of recently, advances in real-world mobility assessment based on body-worn inertial sensors offer the possibility to directly study the impact of BVH-related impairments on daily-life activities and mobility in individual patients [ 16 ]. Whereas lab-based measures commonly focus on the detailed spatiotemporal features of balance and gait deficits, measures from body-worn sensors provide complementary insights into a patient’s overall mobility status and balance capabilities from a macroscopic perspective [ 17 , 18 ]. This information could entail important information to elucidate the ecological relevance of vestibular hypofunction for patients’ activities of daily living and mobility, to establish new clinical endpoints for future clinical trials in BVH, and to supplement currently available screening tools for fall risk assessment in BVH.…”
Section: Introductionmentioning
confidence: 99%